Penggunaan Media Sains Flipbook dalam Pembelajaran IPA di Sekolah Dasarr - Tika Aprilia; Sunardi Sunardi; Djono Djono (Teknodika, 2017)
Advances in technology have driven changes in books into the digital age. Even the Indonesian government, in this case, the Ministry of Education and Culture has implemented it in the form of school electronic books or commonly called BSE. However, ebooks or BSE in schools today, still have weaknesses that should be improved. One of them through e-books in the flipbook format. The purpose of this study is to describe the use of flipbook science media in science learning in elementary schools. This research is a qualitative descriptive study conducted in class V SDN Cemara Dua Surakarta, SDN Mangkubumen Lor No.15 Surakata, and SDN Mangkubumen Kidul No.16 Surakarta in 2016/2017 school year. Data collection techniques are carried out using triangulation of data or sources through observation, interviews, and documentary studies. Data analysis starts from the stage of data collection, data reduction, data presentation, and data verification. The results showed that the use of flipbook science media in science learning in elementary schools can be used optimally if the elementary school has supporting facilities or facilities, such as PCs, LCDs, and sound systems as well as good teacher and student resources in the field of technology. basic computer operating skills. In addition, the use of flipbook media must be used in accordance with the learning objectives to be achieved, so that the effectiveness of the use of flipbook media can be felt optimally